Organizational Culture and Employees Commitment in Civil Service: Exploring the Impact of Organizational Culture on Employees' Commitment in Civil Service (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The paper examined organizational culture and employees’ commitment in civil service. It describes organizational culture as the set of values, beliefs and performance patterns that shapes employee’s behavior and forms the core individuality of the organization. The research question addressed the extent of the relationship among organizational culture and employees’ commitment civil service. A research implement tagged `Organizational Culture and Employees Commitment survey was used for the generation of primary data. A pilot test-re-test study was conducted on 30 randomly selected respondents who are not involved in the study, to ensure the validity of the questionnaire, using the data achieve; a reliability coefficient of 0.83 was calculated using Pearson product moment connection analysis representative a high degree of dependability of the research instrument. Data collected were analyzed using expressive and inferential statistics. The expressive statistics used in the study include occurrence counts and percentages. Results from the data analysis indicated that important relationship exists among organizational culture and employees ‘commitment while important differences were observed in the commitment of employees of dissimilar sex, ages and length of service in civil service. It therefore recommends between others: encouragement of work teams between employees, training and re-training of employees, improvement in the reward system, improvement of internal communication channels and employees participation in decision making.